TACE-HAIC versus HAIC combined with TKIs and ICIs for hepatocellular carcinoma with a high tumor burden—a propensity-score matching comparative study - Wu, Chunxue; Dong, Yunlong; Li, Xinge; Shao, Wenbo; Wang, Guangshun; Wu, Huiyong; Chang, Xu (Frontiers in Immunology, 2025)
PurposeThe present study aimed to comparatively examine transarterial chemoembolization (TACE) plus hepatic arterial infusion chemotherapy (HAIC) in combination with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) versus HAIC alone in combination with TKIs and ICIs for efficacy and safety in individuals with high tumor burden (major portal vein tumor thrombosis [PVTT] Vp3–4 or/and tumors larger than 10 cm) hepatocellular carcinoma (HCC).MethodsTotally 363 inoperable HCC cases with high tumor burden administered TACE-HAIC plus TKI and ICI (TACE-HAIC combination group, n=119) or HAIC plus TKI and ICI (HAIC combination group, n=244) were recruited between October 2020 and January 2024, and propensity score matching (PSM) was utilized for matching patients. Overall survival (OS), progression-free survival (PFS), objective response (ORR), disease control (DCR) rates, and safety signals were assessed.ResultsFollowing PSM (1:2), 87 cases in the TACE-HAIC combination group were matched to 143 cases in the HAIC combination group. Median OS (26.8 vs. 19.1 months, p = 0.233) and PFS (11.17 vs. 9.01 months, p = 0.133) were similar in the TACE-HAIC and HAIC combination groups. ORRs were 58.0% and 64.4% in the HAIC and TACE-HAIC combination groups, respectively (p = 0.341). DCR were 90.9% and 94.3% for these groups, respectively (p = 0.360). Both univariate and multivariate analyses revealed no differences between the two groups pre- and post-matching. The commonest adverse events (AEs) included thrombocytopenia, hypertension, and increased AST (aspartate aminotransferase) and ALT (alanine aminotransferase) of any grade pre- and post-PSM.ConclusionsFor HCC patients with high tumor burden, HAIC demonstrates comparable efficacy to TACE-HAIC both in combination with TKIs and ICIs. Therefore, HAIC should be the preferred local therapeutic strategy over TACE-HAIC in HCC patients with high tumor burden.